Dr. Lani's no-nonsense bone health guide : the truth about density testing, osteoporosis drugs, and building bone quality at any age - Simpson, Lani (Hunter House, an imprint of Turner Publishing Company, 2014)
"Part whistle-blower book, part bone health bible, [this item] exposes [what the author sees as] the shocking difficulty involved in getting an accurate bone density reading and the serious risks of long term use of the most recent osteoporosis medications ... Simpson, both a Doctor of Chiropractic and a Certified Clinical Densitometrist, cuts through the confusion and inaccuracies surrounding osteoporosis to explain her whole-body approach to bone health, which includes discussions of digestive health, diet, supplements, and exercise"--